Studies Toward the Creation of an Urban Mobility Environment in the Anhangabaú Valley: A Design Inquiry (London Journal of Research In Humanities and Social Sciences, 2025)
This paper investigates potential architectural configurations for mobility infrastructure in the Anhangaba Valley So Paulos preeminent historic public space by critically engaging with its extensive urban accessibility and framing mobility networks as the foundational structuring element of metropolitan urban cores. The analysis foregrounds the historical significance of the Anhangaba and its environs, acknowledged as the inaugural modern centrality within So Paulo and a constitutive component of the metropolitan mobility network. Addressing mobility within the Anhangaba demands a critical examination of the different urban levels and the stratified spatial flows converging upon this pivotal public realm. A coherent articulation between this structural framework and the existing vehicular and pedestrian networks, particularly those channeling movement toward public transit nodes, must be established.Consequently, the hypothesis advanced herein posits that the sites latent accessibility can engender an integrated "mobility environment," supplanting the prevailing paradigm of fragmented transport interchanges. The inquiry engages with prior transformative interventions assimilated into the valleys morphology, notably the vehicular underpass and peripheral Metro stations, which remain spatially and functionally disjunct from the Central Areas urban fabric. The imminent introduction of Metro Line 19-Celeste, with two new stations within the Anhangaba, assumes critical importance within this proposition, given the catalytic potential of a metro infrastructure in reasserting the sites metropolitan scale. Thus, the metro system is theorized as an agent of urban transformation. The methodological approach underscoresthe imperative of measured intervention within a consolidated urban tissue. Architectural design is operationalized as an epistemic instrument, with projective experimentation serving as an analytical mechanism to diagnose constraints inherent to antecedent schemes. Representational techniques, deployed as critical mediations, facilitate the analysis of kinetic, topographic, and circulatory dynamics, reinforcing designs constitutive role within an iterative process of urban inquiry.
Keywords: morality.; history; memory; Nietzsche; animality; forgetfulness; unhistorical; suprahistorical; overhuman; landscape; Archaeology; Lithics material culture; Serra Negra; Southern Espinha篠Range; linguistic diversity.; counter-hegemonic forces; language choice; linguistic needs; ambivalence.; Phenomenology; experience; National Learning Camp; Out-of-field; Family businesses; tourism products; beach vendors.; distributive law; the right to deferred exchange; the triad; monetary capital